PENGARUH HIGH INTENSITY INTERVAL TRAINING DENGAN RASIO PERBANDINGAN WAKTU KERJA DAN WAKTU ISTIRAHAT 1:3 TERHADAP VO2MAX PADA SISWA EKSTRAKURIKULER SEPAKBOLA SMP PGRI 1 ULUJAMI PEMALANG - Utomo, Pungkas Setyo; Sartono, Sartono (STKIP Melawi, 2025)
Abstract: This study aims to determine the effect of high intensity interval training with a ratio of work time to rest time of 1:3 on increasing VO2max in extracurricular football students at SMP PGRI 1 Ulujami Pemalang. The research design used is an experimental research approach, namely the experimental activity begins by giving treatment to the subject which ends with a test